FAKTOR YANG BERHUBUNGAN TOTAL FOOD LOSS AND WASTE (FLW) PADA KARYAWAN PT. CAMILOPLAS JAYA MAKMUR SELAMA PANDEMI COVID-19 - Nur Azizah; Prita Dhyani Swamilaksita; Harna Harna; Putri Ronitawati (Jurnal Gizi dan Pangan Soedirman, 2021)
The implementation of large-scale social restrictions during the COVID-19 pandemic has made employees do their work at home so they spend more time ordering food online. This will lead to bad habits that cause food loss and waste (FLW) because the food available at home if not consumed will be wasted. This study aims to determine the factors related to total food loss and waste (FLW) in PT Camiloplast Jaya Makmur employees during the COVID-19 pandemic. The research method is quantitative with a design cross-sectional. Engineering samples total sampling.The analysis of this study used the chi-square. Data were collected using the FLW behavior questionnaire and the form estimated food record 3x24 hours. The results showed that there was a relationship between age (p=0.000, OR=14,385) and gender (p=0.000, OR=20,855) to total food loss and waste (FLW) but there was no relationship between knowledge (p=0,139), income (p=0,826), food selection (p=0,332), lifestyle (p=0,486), frequency of eating (p=0,492) and meal times including breakfast (p=1,000), lunch (p=0,346), and dinner (p=0.476 to the total food loss and waste (FLW). Therefore, employees are expected to be wiser in ordering food online and endeavor to make a list of food to be purchased in order to minimize the occurrence of food loss and waste (FLW).